(3aJhM eUQs - (3eMeO Hf YeQ Hf hGbO GdSgej GdCSdej HGdhdGA, GdeOfj, CHh YHO Gddg, GdhGbOj,J (B207 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf YeQ GdhGbOi QMeg Gddg (B: (3hdbO SeYJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B95s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B196 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs